SMG-2 Is a Phosphorylated Protein Required for mRNA Surveillance in Caenorhabditis elegans and Related to Upf1p of Yeast - Page, Michelle F. (American Society for Microbiology, 1999)
mRNAs that contain premature stop codons are selectively degraded in all eukaryotes tested, a phenomenon termed “nonsense-mediated mRNA decay” (NMD) or “mRNA surveillance.” NMD may function to eliminate aberrant mRNAs so that they are not translated, because such mRNAs might encode deleterious polypeptide fragments. In both yeasts and nematodes, NMD is a nonessential system. Mutations affecting three yeast UPF genes or seven nematode smg genes eliminate NMD. We report here the molecular analysis of smg-2 of Caenorhabditis elegans. smg-2 is homologous to UPF1 of yeast and to RENT1 (also called HUPF1), a human gene likely involved in NMD. The striking conservation of SMG-2, Upf1p, and RENT1/HUPF1 in both sequence and function suggests that NMD is an ancient system, predating the divergence of most eukaryotes. Despite similarities in the sequences of SMG-2 and Upf1p, expression of Upf1p in C. elegans does not rescue smg-2 mutants. We have prepared anti-SMG-2 polyclonal antibodies and identified SMG-2 on Western blots. SMG-2 is phosphorylated, and mutations of the six other smg genes influence the state of SMG-2 phosphorylation. In smg-1, smg-3, and smg-4 mutants, phosphorylation of SMG-2 was not detected. In smg-5, smg-6, and smg-7 mutants, a phosphorylated isoform of SMG-2 accumulated to abnormally high levels. In smg-2(r866) and smg-2(r895) mutants, which harbor single amino acid substitutions of the SMG-2 nucleotide binding site, phosphorylated SMG-2 accumulated to abnormally high levels, similar to those observed in smg-5, smg-6, and smg-7 mutants. We discuss these results with regard to the in vivo functions of SMG-2 and NMD.